Design of Traction Converter for New Generation of Power Centralized EMU - Yi ZHANG; Yongjiang LIU; Bin FAN; Yupeng LI; Chuan BIN (机车电传动)
Power centralized EMU had become a research hotspot in this field because of its remarkable advantages in maintainability, safety and flexible marshalling. In order to meet the top-level technical index requirements of the new generation power centralized EMU system, in this paper, a high integrated lightweight traction converter was designed, then the main circuit topology, working principle, performance parameters and key technologies of the traction converter of the power centralized EMU were introduced, and cooling system design points and the system availability under the faults of high-power traction converter were focused on. The full load ground operation test showed that the converter had good control performance and reliable operation, which met the requirements of overall design and application.